Implementation of the Total Physical Response (TPR) Method with the Help of Flashcards to Teach English Vocabulary - Frita Noviandari; Katharina Rustipa (research, training and philanthropy institution Natural Aceh, 2023)
Teaching vocabulary to children must be engaging and fun to spark their interest and motivate them to learn English, particularly to memorize English vocabulary. To establish pleasurable learning for children, the teacher must discover creative methods and media to encourage students to learn English vocabulary. This study aims to find out the implementation of the TPR method with the help of flashcards to teach English vocabulary at Kindergarten Muslimat NU TA 07 Plantaran and to describe how the TPR method with the help of flashcards can encourage kindergarten students at Muslimat NU TA 07 Plantaran to learn the English vocabulary. This study uses a descriptive qualitative method. Non-participant observation and interviews are conducted as the data collection techniques. The findings show that teaching using the TPR method with the help of flashcards is implemented in three steps: pre-teaching, whilst-teaching, and post-teaching. In teaching and learning, the teacher acts as a model and gives orders while students respond and imitate them with physical movements. Implementation of TPR with the help of flashcards can encourage students' motivation to learn English vocabulary. This can be seen from the behavior of motivated students during learning, including being active, responsive, interested, enthusiastic, responsible, and diligent.